Variants and deformities of atlas vertebrae in Eastern Anatolian people - Kavakli, A; Aydinlioglu, A; Yesilyurt, H; Kus, I; Diyarbakirli, S; Erdem, S; Anlar, Ö (Saudi Med J, 2004)
Objective: At the craniocervical junction, developmental anomalies of the atlas may produce clinical symptoms by compressing on the vertebral artery, particularly during extreme rotational movements of the cervical spine. The aim of the present study was to investigate several varieties and deformities of the atlas vertebra from the skeletal specimens of Eastern Anatolian people. Methods: This study was carried out over a 3-year period, 2000 through to 2002 in the Department of Anatomy, Firat, Yuzuncu Yil and Ataturk University, Turkey. Developmental anomalies and the variants of the first vertebrae were investigated on 86 atlas. Results: Ponticulus posterior was observed with a low frequency on right as 2.3%. The bilateral localization was 10.5% and the left-side localization was 9.3%. Ponticulus lateralis showed an equal localization as 1.2% on the right, 1.2% on the left and 1.2% bilateral. In the present study, a complete subdivision of the joint surface was observed in 11 atlases (12.8%). Processus infratransversarius atlantis with a frequency between 1.2-7%, arthrotic formation and corona atlantis peridentals in 8 cases (9.3%) were also found. Conclusion: The low frequency for fonticulus posterior might be peculiar to the population living in this area.
Keywords: Craniocervical Junction; Ponticulus Posticus; Cervical Vertebra; Diagnosis; Groove; Artery; Bridge